2015
DOI: 10.4103/1463-1741.169698
|View full text |Cite
|
Sign up to set email alerts
|

Impact of overnight traffic noise on sleep quality, sleepiness, and vigilant attention in long-haul truck drivers: Results of a pilot study

Abstract: This study aimed to evaluate the impact of traffic noise along the motorway on sleep quality, sleepiness, and vigilant attention in long-haul truck drivers. This was a randomized, crossover, within-subject controlled study. Healthy long-haul truck drivers spent 6 consecutive nights in a real truck berth with full sleep laboratory equipment. During 3 nights, subjects were exposed to replayed traffic noise alongside motorways, whereas the other 3 nights were without traffic noise. Polysomnography was recorded du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
0
9
0
1
Order By: Relevance
“…Most of the drivers had the opportunity to sleep at home, which is not possible for all long-haul truck drivers. It has been reported that sleeping, e.g., in the truck sleeper cabs or at motorway rest areas may result in disrupted sleep (Popp et al 2015). Second, the accumulation of sleep loss across the study period was operationalized as the sum of daily sleep compared to self-reported sleep need.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the drivers had the opportunity to sleep at home, which is not possible for all long-haul truck drivers. It has been reported that sleeping, e.g., in the truck sleeper cabs or at motorway rest areas may result in disrupted sleep (Popp et al 2015). Second, the accumulation of sleep loss across the study period was operationalized as the sum of daily sleep compared to self-reported sleep need.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it was recently reported that nights with rather low levels (35–45 dB L AEq,indoor,night ) of ground-borne low-frequency noise from railway tunnels led to a reduction in total REM time of around 5–7 min compared to a quiet control night [ 50 ]. Longer REM latencies have been observed during nights with road or rail traffic noise [ 61 , 62 ], although other studies have found shorter REM latencies or no effect [ 63 , 64 ]. The precise function(s) of REM sleep remains controversial, but it may be important for cognition, consolidation of procedural and declarative memories, and synaptic pruning and strengthening [ 65–67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al 35 pointed out that SWS gradually decreased with the increase of CO 2 concentration. Popp et al 62 found out that SE significantly increased in silent condition compared to noise condition. Based on the research conducted above, four initial linear structure models were determined.…”
Section: Three Lessons Conducive To Improving Small Determination Coe...mentioning
confidence: 98%